Moral Questions, Legal Answers, and Biotechnological advances - Godlovich, Glenys (Victoria University of Wellington Law Review, 1998)
Moral Jailing is usually construed as a personal flaw, but there is another construction: where morals Jail people, where our moral precepts are silent. The author of this article argues that this happens nowadays where technological advances, such as genetic engineering in medicine, raise moral questions but get legal answers. By responding to the legal issues involved, the moral questions are pre-empted. This results in answers drawn from legal categories, often with commercial perspectives, but misses the larger moral domain.